Cohort feasibility study of an intermittent pneumatic compression device within a below-knee cast for the prevention of venous thromboembolism. Issue 10 (4th October 2016) - Braithwaite, Irene; De Ruyter, Bernadette; Semprini, Alex; Ebmeier, Stefan; Kiddle, Grant; Willis, Nigel; Carter, John; Weatherall, Mark; Beasley, Richard
Abstract : Objectives: To determine the likely enrolment rate of eligible participants into a randomised controlled trial (RCT) in which a within-cast intermittent pneumatic compression device using Jet Impulse Technology (IPC/JIT) is 1 of 3 possible interventions in a RCT for the prevention of venous thromboembolism (VTE) in the clinical setting of isolated lower limb cast immobilisation. Design: A prospective, open-label feasibility study of the IPC/JIT device placed within a lower limb cast. Setting: Wellington Regional Hospital Fracture Clinic. Participants: Individuals aged 18–70 who presented with a lower limb injury requiring a minimum of 4 weeks below-knee cast immobilisation. Intervention: Placement of an IPC/JIT device within lower limb cast. Outcome measures: The main outcome measure was the proportion of eligible participants who participated in the feasibility study. Secondary outcome measures included adherence to device usage throughout the study, ease of application of the device and adverse events potentially associated with its use. Results: The proportion of potentially eligible participants for the IPC/JIT device was only 7/142 (5%), 95% CI 2 to 9.9. Devices were used for a mean (range) of 4.1 (1.9 to 10.2) hours per day and none of 7 participants had adequate adherence to the device. 3 of the 7 participants suffered an adverse event, including 1 deep vein thrombosis, 2 dorsal foot ulcer and 1 skin maceration. Conclusions: A within-cast IPC/JIT device is unlikely to be a feasible randomisation arm for a RCT assessing possible interventions for the reduction of VTE risk in the clinical setting of lower limb injury requiring below knee cast immobilisation for a minimum of 4 weeks. Trial registration number: ANZCTR 12615000192583 .